Creating data-driven culture in a Finnish B2B software company's marketing department - Nummela, Pinja (2023)
Generating insights and actions out of data has become one of the most important jobs for marketing departments. While companies are struggling with finding the right data to gather, some of the main problems to become a data-drive-driven company are cultural. The goal for this study is to understand how a data-driven culture is instilled in employees and what the company culture should be like to make the adoption of the new mindset as easy as possible. The research also seeks to identify potential challenges and barriers to the adoption of a data-driven marketing culture. The research is conducted for the Finnish B2B software company where the researcher worked meanwhile. The framework of this study was based on earlier studies and theories of data-driven culture and change management. The empirical material of the study was collected interviewing marketing professionals across the organisation and from two marketing agencies. The qualitative study method is chosen to acquire a deep understanding of the subject under study. In the study the inductive approach was used, wherein the discovered findings were closely tied to the gathered data. Data-driven marketing has not previously been studied from a corporate culture perspective, so this study opens a whole new perspective on the adoption of data-driven marketing. The study provides practical recommendations to the case company on how to facilitate the implementation of the new working methods. The study found that a company needs both clear communication and a strong learning culture to succeed in adopting data-driven marketing. Possible challenges include difficulties in team communication, fragmented data across different systems, and managers' inability to effectively communicate and lead teams, resulting in decreased employee motivation